Secondary forests in the Philippines: formation and transformation in the 20th century - Lasco, R.D.; Visco, R.G.; Pulhin, J.M. (2001)
Secondary forests are the largest and most dynamic natural forest ecosystems in the Philippines. This paper examines the characteristics and dynamics of secondary forests in the country. In the last century, the country lost 50% of its natural tropical forest cover. At present, the major land cover types in terms of areal coverage are upland farms, secondary forests, protected forests, brushlands, grasslands and tree plantations. The two most dominant types of secondary forests are post extraction secondary forests and swidden fallow secondary forests. The former stems from legal and illegal logging, which are ultimately rooted in corruption, poverty and high population pressure. At present, post extraction secondary forests are the main source of wood products of the country. Although secondary forests initially increase as a result of heavy commercial logging, they subsequently decrease due to degradation to brushland and conversion to agriculture. Swidden fallow secondary forests are generally associated with indigenous cultural communities who derive many ecological and socio economic benefits from them. However, there are very limited quantitative data available on these forests, including areal coverage. The paper emphasises the need for research efforts directed at the sustainable use and conservation of secondary forests in the Philippines.